Parents Involvement in the Education of their Children: Indicators of Level of Involvement - Sreekanth, Yagnamurthy (International Journal about Parents in Education, 2023)
Parents have incessant interest in the education of their children. But, what makes some parents different is their ability to go beyond implicit and conventional norms of parental responsibility for the well being of their children. Parental involvement is subjective in nature and difficult to evaluate. However, in the present paper the author provides a mechanism through which parental involvement is evaluated from an ethnocentric approach. In this study, parents were selected by teachers and interviewed on the basis of a semi-structured questionnaire. A brief note of case studies leading to a conceptual frame of parental involvement is presented in this paper. The parental involvement here is connotated as going beyond one’s own capacity through perseverance and compromise of one’s own interest for the education of children, which may have a positive impact on other children and parents.